Collaboration and emotions to the test: the experience of FILe volunteers in hospices - Mascagni, Giulia (Acta Biomedica Atenei Parmensis, 2016)
Background and aims: This study seeks to provide an in-depth analysis of care-based interaction in the experiences of volunteers working in lenitherapy (pain therapy) through the case study of hospices in Florence, Italy. Method: A qualitative method of data collection was chosen: the field research made use of open-ended questionnaires distributed to trained but unspecialised volunteers (V = 32) and to volunteers with hospital-based medical expertise (PV = 35) acting for the Italian Lenitherapy Foundation (FILe) and operating in hospices within the ex-ASL (Local Health Unit) of Florence. Results: By analysing the 67 questionnaires collected, it has been possible to reconstruct and interpret the interactional dynamics that exist between the various figures present within a hospice, bringing into focus the most salient aspects of both the organisational context and emotional setting. Conclusions: The research experience, by highlighting everyday unseen aspects that are inaccessible to an ‘internal’ eye, has made it possible to better characterise the dynamics of unsuccessful collaboration between team members and potential areas of conflict. Finally, where these dynamics have been observed, an attempt has been made to outline priorities for change and possible directions to be taken, so as to promote defusing actions and restore synergy and fluidity to the FILe system.